Sobre a constituição do sujeito: uma análise comparativa entre a psicologia sócio-sociologia do conhecimento de berger e luckmann - Daniel Júnior, Geraldo Magela (2007)
This study investigated how the process of the constitution of the subject is interpreted in the formulations of the founders of socio-historical psychology (Lev S. Vigotski, Alexei N. Leontiev and Alexander R. Luria) and in the sociology of knowledge of Peter Berger and Thomas Luckmann. These two theoretical perspectives, despite having different philosophical formulations as ontological and epistemological intentions (socio-historical psychology, historical dialectical materialism; the sociology of Berger and Luckmann and phenomenology) arrive, however, at the same basic conclusion about the social nature of the subject. The objective of the study, therefore, was that of identifying the differences and convergences between the two perspectives and then, try to determine the possibility of a theoretical synthesis between them in relation to the constitution of the subject. At the same time, we intended to analyse the implications of this possible synthesis in order to comprehend the manner in which the ideology functions in human societies as thought by Louis Althusser and Alípio de Sousa Filho. We arrived at the conclusion that, despite being incompatible from the ontological and epistemological points of view, a synthesis is possible between socio-historical psychology and the sociology of knowledge of Berger and Luckmann in relation to the conception of society and the comprehension of the process of the constitution of the subject. Starting from the philosophical intentions of socio-historical psychology, it is possible to incorporate, enriching points such as: Berger s and Luckmann sconception of society and the interpretation of the process of constitution of the subject. This possible synthesis, when interpreted in light of the reflections of Althusser and Sousa Filho on the phenomenon of ideology in human societies, is constituted in a real unveiling of the concrete provisos by which the ideology acts in human societies in order to transform biological examples of the human species in specific social subjects